Coach Communication Skills and Athlete Performance: A Systematic Literature Review of Verbal, Nonverbal, and Relational Mechanisms in Sport - Irwansyah Siregar; Fahmy Zidhan Kurniawan; Cut Muetia Balqhis; Nurrodiah Siregar; Yunus Abadi; Zahrian Perangin-angin; Fuji Amanda; Rinaldi Rinaldi (Indonesian Institute For Counseling, Education and Therapy, 2026)
Interpersonal communication between coaches and their athletes has always been considered a key factor for athlete development, but very little empirical work has so far explored the role of communication in athletic performance as well as psychological outcomes with respect to coach's communication behaviors, the literature has still been confined within the limits and boundaries of each field of study without sharing the insights with or across different disciplines. The systematic review that follows aims to present a summary of the peer-reviewed research on the coach communication skills and their effect on athlete performance, motivation, and well-being. According to the PRISMA 2020 guidelines, this work has tried to trace out how the coach's verbal, bodily (non-verbal), and relational (the kind of relationship between the parties) communication aspects bring about different performance or outcome patterns in the athletes as well as to examine if these different mechanisms change depending on the cultural or contextual aspects. By following Scopus as a retrieval vehicle of literature, one got in the hand 108 references which initially were considered to fit to some degree the criteria of the research. However, it was not possible to find suitable duplicates of such works that had no other duplicates, so 108 references were first checked. Then, retracted publications, works with incomplete bibiographical info, or studies with a different disciplinary angle were 35 of them rejected. The 73 remaining documents went through the stage of being evaluated for their relevance in terms of full-text access based on the inclusion/exclusion rules previously set and out of them, 23 ones were rejected for the reason that there wasn't a direct enough connection to coach-athlete communication. Finally, qualitative analysis was carried out from 50 articles. Four major themes were identified. One, that verbal guidance and encouragement strongly relate to the self-efficacy of athletes together with their overall motivation and quick performance while the extent to which such effects will be seen also depends upon when the feedback takes place, its nature, and the gender of the speaker. Two, gestures, expressions as well as the coach's mental setting, especially through visualization, referee's behavior, etc., all have to do with the athletes' sense of psychological safety and emotional balance. Three, the level of quality in the coach and athlete communication not only serves as a bridge between transformational leadership and team cohesiveness but also influences the direction of performance at organizational level. Four, factors such as culture, generational and tech-wise context, including but not limited to involvement from parents, religious practices, different gender norms, and use of virtual or AI-mediated coaching tools, significantly changed the way communication was delivered and understood. This review of research work theoretically enriches the models describing coach-athlete relationship dynamics in that it highlights the physical aspect of communication to be trained separately from other relational elements, rather than seeing it as part of general communication skills of a relational nature. In practice, it has provided coaching educators an opportunity to develop coach education programs with evidence-based feedback delivery systems, nonverbal communication awareness trainings, and culturally sensitive communication protocols. Besides this, future studies need to look more deeply into the effects of coach feedback and communication styles on athletes through longitudinal research and experimental paradigms, employ communication measurement instruments that are standardized, and also, include less-represented groups such as young athletes, athletes with disabilities, and gamers in the research design and sample of the study